2019
DOI: 10.1111/1365-2664.13503
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and regime shifts: Do novel communities impede ecological recovery in a historically metal‐contaminated stream?

Abstract: 1. Novel communities that result from exposure to contaminants and other anthropogenic stressors often persist in ecosystems that have experienced regime shifts.Because these systems may not return to pre-disturbance conditions after removal of a stressor, understanding the ecological consequences of regime shifts has important implications for how restoration success is defined. Long-term observational studies can potentially identify regime shifts in disturbed ecosystems; however, experimental approaches may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 68 publications
1
14
0
Order By: Relevance
“…Although the overall diversity of dominant plants did not differ between impounded and tidal brackish wetlands, the species identity and functional attributes of dominant plants did differ. As species presence, relative abundance, and functional traits can alter ecosystem function (Lefcheck et al 2015, Stotz et al 2019), management‐induced changes in dominant plant composition likely affect important ecosystem processes, including carbon cycling (Kroeger et al 2017), climate change resilience (Stagg et al 2016), and long‐term restoration potential (Wolff et al 2019). As the functional traits of rhizomatous perennial graminoids found in tidal brackish wetlands and non‐rhizomatous annual graminoids or perennial forbs found in impounded brackish wetlands are not equivalent, changes in dominant species could lead to important, but understudied, shifts in ecosystem function (Hooper et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Although the overall diversity of dominant plants did not differ between impounded and tidal brackish wetlands, the species identity and functional attributes of dominant plants did differ. As species presence, relative abundance, and functional traits can alter ecosystem function (Lefcheck et al 2015, Stotz et al 2019), management‐induced changes in dominant plant composition likely affect important ecosystem processes, including carbon cycling (Kroeger et al 2017), climate change resilience (Stagg et al 2016), and long‐term restoration potential (Wolff et al 2019). As the functional traits of rhizomatous perennial graminoids found in tidal brackish wetlands and non‐rhizomatous annual graminoids or perennial forbs found in impounded brackish wetlands are not equivalent, changes in dominant species could lead to important, but understudied, shifts in ecosystem function (Hooper et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…CC-BY-NC-ND 4.0 International license available under a was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. It is made The copyright holder for this preprint (which this version posted May 2, 2020. ; https://doi.org/10.1101/2020.04.30.071522 doi: bioRxiv preprint macroinvertebrate membership between upstream and downstream locations previously reported for this same location (18).…”
Section: Discussionmentioning
confidence: 78%
“…CC-BY-NC-ND 4.0 International license available under a was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. It is made The copyright holder for this preprint (which this version posted May 2, 2020. ; https://doi.org/10.1101/2020.04.30.071522 doi: bioRxiv preprint Previous investigations have shown that experimental metal exposure resulted in much greater effect on composition from macroinvertebrate communities sourced from sites upstream of California Gulch (18). In this mesocosm experiment we expected to see greater changes in microbiome membership of upstream microbiomes in response to the metal treatments, since this site has historically had lower metal exposure and we anticipated the microbes would be more sensitive to metal stress.…”
Section: Discussionmentioning
confidence: 99%
“…Only a minority of species, which we called 'resilients', showed some recovery to date. The novel community that emerged from the climate shift of the 1990s, with many once characteristic species lost, reduced complexity, biotic homogenization, greater diversity, and domination by alien species, may be able to persist [70], and there is little opportunity to go back for ecosystems under altered regime [16]. Recent analyses of Ligurian Sea temperature suggest that another phase of rapid warming is occurring, 2014 to 2018 having been the warmest years on records [28,46], thus conforming to the expected further rapid warming over the whole Mediterranean Sea [71,72].…”
Section: Discussionmentioning
confidence: 99%